PD-1 Inhibitors Could Improve the Efficacy of Chemotherapy as First-Line Treatment in Biliary Tract Cancers: A Propensity Score Matching Based Analysis - Gou, Miaomiao; Zhang, Yong; Liu, Tiee; Si, Haiyan; Wang, Zhikuan; Yan, Huan; Qian, Niansong; Dai, Guanghai (Frontiers in Oncology, 2021)
Background There was limited treatment for advanced biliary tract cancers (BTCs) including Intrahepatic cholangiocarcinoma, extrahepatic bile duct cancer, gallbladder cancer. Hence, we compared the efficacy and safety of PD-1 inhibitor plus chemotherapy and chemotherapy alone as first line treatment in patients with advanced BTC. Methods We retrospectively reviewed BTC patients from oncology department of Chinese PLA general hospital receiving PD-1 inhibitor with chemotherapy (Anti-PD-1+C group) or chemotherapy alone (C group). To balance for potential baseline confounding factors, the Propensity Score Matching (PSM) (1:1) was performed. Progression-free survival (PFS) was analyzed using Kaplan–Meier survival curves with log-rank tests. Objective response rate (ORR), disease control rate (DCR) and safety were also analyzed. Results In all, 75 patients who received PD-1 inhibitor (including Pembrolizumab, Nivolumab, Sintilimab, Toripalimab) plus chemotherapy and 59 patients used chemotherapy alone were included in the study. After matching, there was no significant difference between the two groups for baseline characteristics. Within the matched cohort, the median PFS was 5.8m in Anti-PD-1+C group, significantly longer than C group which was 3.2m (HR: 0.47 ,95% CI 0.29 to 0.76, P = 0.004). ORR was 21.7% and DCR were 80.4% observed in Anti-PD-1+C group while ORR was 15.2% and DCR was 69.6% in C group respectively. No significant difference was found for ORR and DCR comparing the two groups (P=0.423, P=0.231). Grade 3 or 4 treatment-related adverse event (AEs) occurred in Anti-PD-1+C group were hypothyroidism (n=3, 6.5%), rash (n=2, 4.2%), hepatitis (n=1, 2.2%). There was no AE related death. Grade 3-4 leukopenia was similar between the two groups (4.3% vs. 6.5%). Conclusions Anti-PD-1 therapy plus chemotherapy prolonged the mPFS compared with chemotherapy alone in advanced BTC with controllable AE. Further clinical trials were needed and we conduct the phrase II clinic trail of Toripalimab with AS (TSA-01 study) is ongoing (clinical registration number: NCT04027764).